2016
DOI: 10.7771/1932-6246.1184
|View full text |Cite
|
Sign up to set email alerts
|

Situative Creativity: Larger Physical Spaces Facilitate Thinking of Novel Uses for Everyday Objects

Abstract: People often use spatial metaphors (e.g., think "laterally, " "outside the box") to describe exploration of the problem space during creative problem solving. In this paper, we probe the potential cognitive underpinnings of these spatial metaphors. Drawing on theories of situative cognition, semantic foraging theory, and environmental psychology, we formulate and test the hypothesis that larger physical spaces can facilitate divergent (but not convergent) processes in problem space exploration. Across two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The size of the physical space is also deemed important. The study of Chan and Nokes-Malach ( 2016 ) showed that participants in a larger room produced more novel alternative uses for everyday objects than participants who were assigned to a smaller room. According to the authors, the open environment of the large room stimulated participants to explore alternative uses more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the physical space is also deemed important. The study of Chan and Nokes-Malach ( 2016 ) showed that participants in a larger room produced more novel alternative uses for everyday objects than participants who were assigned to a smaller room. According to the authors, the open environment of the large room stimulated participants to explore alternative uses more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…I conducted a statistical power analysis for sample size estimation using G*Power 3.1. With reference to the effect sizes reported in previous studies examining the effects of different physical environments on divergent thinking [ 21 , 25 , 30 ], I assumed the effect size in the present study to be large ( f = .40) using Cohen’s [ 40 ] criterion. With alpha = .05 and power = .80, the projected sample size needed with this effect size was N = 66.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research in real-world settings has shown that rooms that activate free concepts, such as broad rooms, high ceilings, or disorderly rooms, promote divergent thinking [ 21 , 25 , 29 ]. Similarly, in the present study, the VR environment of the visually open coast with no ceiling and an unobstructed view resulted in higher AUT scores because it activated the concept of freedom compared with the visually closed laboratory surrounded by ceiling and walls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…experience or positive affect might be responsible for part of the "generation effect, " where generation leads to better long-term memory for solutions. Finally, the paper by Chan and Nokes-Malach (2016), "Situative ceativity: Larger physical spaces facilitate thinking of novel uses for everyday objects, " discusses how problem solving contexts might affect problem solving performance across a variety of tasks, including alternative uses, novel shape invention, remote associates, and series completion.…”
Section: Jennifer Wileymentioning
confidence: 99%